2012
DOI: 10.5539/elt.v5n3p230
|View full text |Cite
|
Sign up to set email alerts
|

A Case for Direct and Indirect Feedback: The Other Side of Coin

Abstract: The use of WCF is a striking necessity in learning of English as a foreign language. If teachers and students can manipulate well the use of written feedback, both parties will benefit. This research looked at the types of feedback given to EFL students during a16-week study. For the purpose of current survey eighty students enrolled freely where they were randomly assigned into two equal treatment groups. Core components of the treatment included having students write a 250-word composition each session, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 34 publications
3
15
0
Order By: Relevance
“…Because teachers are primarily concerned with long-term skill development, we believed that teachers would prefer providing indirect and metalinguistic feedback while students would prefer receiving direct feedback. This belief is informed by previous research by Hartshorn and Evans (2012), Hashemnezhad and Mohammadnejad (2012), and Ebadi (2014), who made connections between WCF and metalinguistic language skill development.…”
Section: Hypothesesmentioning
confidence: 93%
See 1 more Smart Citation
“…Because teachers are primarily concerned with long-term skill development, we believed that teachers would prefer providing indirect and metalinguistic feedback while students would prefer receiving direct feedback. This belief is informed by previous research by Hartshorn and Evans (2012), Hashemnezhad and Mohammadnejad (2012), and Ebadi (2014), who made connections between WCF and metalinguistic language skill development.…”
Section: Hypothesesmentioning
confidence: 93%
“…As more researchers move beyond the initial questions on the effectiveness of WCF, recent studies have called for research into situational application, student and teacher attitudes and expectations of feedback, the context in which the feedback is given, and greater sample sizes of collected data (Amrhein & Nassaji, 2010;Norouzian & Farahani, 2012;Sayyar & Zamanian, 2015). The potential metacognitive benefits of indirect feedback suggest that less direct feedback, i.e., providing an indication of the location and/or type of error to help the learner self-correct, is important to develop the higher-level writing abilities of students (Lalande, 1982;Hartshorn & Evans, 2012;Hashemnezhad & Mohammadnejad, 2012;Ebadi, 2014;Mansourizadeh & Abdullah, 2014). Less direct feedback, however, may be incompatible with some learners' preference for teacher-centered instruction.…”
Section: Introductionmentioning
confidence: 99%
“…It is also suggested that indirect CF is a better means to assist learners in improving grammatical accuracy because studies have shown that indirect feedback enables learners to be involved in a deeper processing of the CF (e.g., Ferris, 2006;Lalande, 1982). On the contrary, other studies suggest that direct CF may be more effective in assisting learners improve linguistic accuracy in written work (e.g., Bitchener & Knoch, 2010;Hashemnezhad & Mohammadnejad, 2012). Since direct CF provide learners with the correct forms for the errors committed, it may be more helpful for them to make corrections and revise their written work The diverse findings in the studies discussed here imply that more empirical evidence is needed to inform teachers and researchers in making a resounding evaluation on the effectiveness of different CF options.…”
Section: Types Of Corrective Feedbackmentioning
confidence: 96%
“…Indirect feedback affords opportunities for “guided‐learning and problem solving” (Lalande, , p. 143) but direct feedback is considered preferable if learners are unable to correct their own errors. While some studies have reported no difference in the effect of direct and indirect WCF when rewriting (e.g., Ferris, ) or in new pieces of writing (Semke, ; Robb, Ross, & Shortreed, ; Vyatkina, ), other studies have found that direct WCF is more effective than indirect WCF (Bitchener & Knoch, ; Hashemnezhad & Mohammadnejad, ; Frear, ). These studies vary enormously in at least four ways: how these two types of feedback were operationalized, whether the feedback was focused or unfocused, the nature of the writing tasks investigated, and the kinds of learners they investigated.…”
Section: Review Of the Literaturementioning
confidence: 99%